Utilizing Farasan Architectural Heritage to enrich the aesthetic values in the contemporary tourist buildings: الاستفادة من التراث المعمارى الفرسانى لإثراء القيم الجمالية فى المبانى السياحية المعاصرة - Marwa Mahmoud Galal Mohamed Osman, Rania Ragab Abdel Maksoud Mohamed (Journal of engineering sciences and information technology, 2019)
The contemporary tourist buildings provide a unique visual experience for its visitors. A vision combined with the heritage sites around it affords a closer connection between the past and the present, confirming its identity and making it special. The architectural heritage is a rich source of fine values to enrich the tourist buildings. Hence, the idea of research arises as the Farasan Islands is a unique tourist area with its heritage buildings of special architectural values, The problem of research is how the artistic treatment of traditional decorations in Farasan as a source of innovative designs for the tourist buildings, and the research aims to study the aesthetics of Farasan’s architectural heritage , study its aesthetic values and design of the interfaces of tourist buildings and its fabrics furnished using computer program ,The importance of research to highlight the archaeological sites of Farasan and to guide the society towards the importance of its architectural and cultural heritage, and also benefit from it in contemporary architecture by following a historical approach, analytical for the architectural vocabulary of the heritage buildings of Farasan and an applied technical approach to create innovative designs to enrich its touristic building .The researchers have reached through the results of the research: The vocabulary of the heritage in farasan architecture rich with formative elements to enrich the design of the architectural facades of tourist buildings and the design of its furnishing fabrics , where the researchers used design solutions inspired by the study of the architectural heritage of Farasan combines the originality and modernity, which gives the tourist buildings in the islands of Farasan unique identity.